War-Time Destruction and the Persistence of Economic Activity - Daniela Glocker; Daniel Sturm (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
A key prediction of a large class of theoretical models is that the location of economic activity is not necessarily determined by fundamentals. To test the empirical relevance of these ideas requires a natural experiment in which a large but ultimately temporary shock dislocates economic activity. Following Davis and Weinstein (2002) a number of papers have used war-time destruction as such a temporary shock. In this paper we revisit this debate and use the cities that were part of pre-war Germany and become part of Poland after the Second World War as a natural experiment. We show that also in this case cities recover surprisingly fast from the war-time shock despite heavy destruction and the expulsion of the entire population. Our results suggest that either the location and size of cities is indeed determined by fundamentals or that even heavily destroyed cities are rebuilt because the ruins contain valuable surviving structures. We provide suggestive qualitative evidence that the second interpretation is more likely correct.
Keywords: F14; F15; N74; 330